Impact of war-associated factors on spread of sexually transmitted infections: a systemic review - Kvasnevska, Yulia; Faustova, Mariia; Voronova, Kseniia; Basarab, Yaroslav; Lopatina, Yaroslava (Frontiers in Public Health, 2024)
Introduction Statistical data indicate a link between war and the spread of sexually transmitted infections (STIs), then it is necessary to carefully analyze the factors that directly affect the identified pattern in order to overcome this problem. Therefore, the purpose of the study was to systematically analyze the factors that influence the spread of STIs during war. Methods The study included all original research articles and meta-analyses on the impact of war on the spread of sexually transmitted infections that met the following eligibility criteria: (1) articles published exclusively in English; (2) articles published in the period 2013–2023; (3) studies with quantitative, qualitative or mixed design. The search for relevant literature was conducted using four databases: PubMed, Embase, Web of Science, and Ebsco. Results The articles selected for our systematic review had different research designs and were mainly published as original studies (n = 8) and literature reviews (n = 6). As a result of the evaluation of the selected articles for the systematic review, the authors identified migration, a decrease in access to health care, difficult access to contraception, sexual violence as the most frequent factors directly affecting the spread of STIs during the war. Conclusion This systematic review systematizes data on the impact of hostilities on the spread of STIs and outlines the main factors that contribute to the dissemination of pathogens far beyond the territory at the epicenter of the conflict. Systematic review registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023479808, CRD42023479808.